AlN gradient interlayer design for the growth of high-quality AlN epitaxial film on sputtered AlN/sapphire substrate. Issue 41 (3rd October 2018) - Tan, Bo; Hu, Jiahui; Zhang, Jun; Zhang, Yi; Long, Hanling; Chen, Jingwen; Du, Shida; Dai, Jiangnan; Chen, Changqing; Xu, Jintong; Liu, Fuhao; Li, Xiangyang
Abstract : In this study, we proposed a novel method to grow high-quality AlN films on sputtered AlN/sapphire substrates by designing an AlN gradient interlayer (GIL-AlN). Abstract : In this study, we proposed a novel method to grow high-quality AlN films on sputtered AlN/sapphire substrates by designing an AlN gradient interlayer (GIL-AlN). The epitaxial growth kinetics and growth mechanism were studied in detail, which are responsible for the effects of GIL-AlN layers on the morphology evolution, crystal quality and in-plane biaxial stress of AlN films by varying temperature and/or V/III ratio gradient. The results showed that the insertion of a temperature and V/III ratio gradient GIL-AlN promoted the initial coalescence of small sputtered AlN grains, which finally grew into larger and low-density AlN islands in consistent c -axis orientation, leading to less threading dislocations and biaxial tensile stress in the upper HT-AlN films. Finally, we obtained a 1.5 μm high-quality crack-free AlN film with an atomically smooth surface, and the full width at half-maximum values of (0002) and (101̄2) rocking curves were 197 and 435 arcsec, respectively, in an almost stress-free state. This GIL-AlN method provides a possible way to improve the surface cracks and quality of AlN films deposited on sputtered AlN/sapphire substrates, which hold great promise for commercialization in AlN-based devices.